THE HISTORY OF KNIFE PREPARATION CRAFTSMANSHIP IN THE FERGANA VALLEY - Z. Esonov; A. Amanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the features of the knife preparation craftsmanship tradition of the Fergana valley. Historical sources and field expedition materials analyzed the peculiarities of the region’s knives. The main focus is on identifying the historical factors that created the traditions of Fergana Valley Knife School. The content of a series of ethnolectal methods in knife-knitting.